Investigating mobility and highland occupation strategies during the Early Holocene at the Cuncaicha rock shelter through strontium and oxygen isotopes. (June 2018) - Chala-Aldana, Döbereiner; Bocherens, Hervé; Miller, Christopher; Moore, Katherine; Hodgins, Gregory; Rademaker, Kurt
Abstract: Results from the recent excavations at the Cuncaicha rock shelter (4480 m above sea level) suggest a successful colonization of the Andean highlands by groups of foragers during the Terminal Pleistocene and Early Holocene. The discovery of Early and Late Holocene human remains buried in the site brings new opportunities to assess mobility and occupation strategies during this period. In this study, isotopic analysis of strontium ( 87 Sr /86 Sr) and oxygen (δ 18 O) in faunal and human dental enamel helped to identify the most likely areas where humans obtained food and consumed water during their formative years. Collection of modern plant and water samples also helped to define a reliable background for the mobility analysis within the study area. 87 Sr /86 Sr ratios and δ 18 O on dental enamel showed that Early Holocene humans lived within the Pucuncho Basin and obtained most of their resources from there. Isotopic analyses are an important step for modeling the mobility patterns of the Early Holocene occupants of Cuncaicha. Highlights: Isotopic analysis of Sr and O detailed mobility and occupation strategies of Early Holocene hunter-gatherers in southern Peru. Early Holocene humans from Cuncaicha spent their formative years at high elevation. Cuncaicha rock shelter can be considered as a base camp.